Pengaruh Penggunaan Media Pembelajaran Kahoot Terhadap Hasil Belajar Dasar-Dasar Akuntansi Siswa Kelas X Jurusan Akuntansi dan Keuangan Lembaga di SMK Negeri 1 Singaraja - Tarigan, Maissy Christiani; Santi, Ni Wayan Ayu (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine the effect of using Kahoot learning media on the learning outcomes of accounting basics significantly. This research design is a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The population in this study is 106 class X students majoring in Accounting and Financial Institutions in 2023/2024, with a total sample of 70 students divided into 2 groups, namely 35 experimental class students and 35 control class students. The sampling technique uses a simple random sampling technique. Data collection techniques used in the study used study test results, interviews, and documents. The data were analyzed by paired sample t-test. The results of this study show that the use of Kahoot learning media has a significant effect on the learning outcomes of the basics of accounting for grade X students majoring in Accounting and Financial Institutions at SMK Negeri 1 Singaraja.